Quality investing in an Australian context. (November 2014) - Gallagher, David R; Gardner, Peter A; Schmidt, Camille H; Walter, Terry S
This study extends an examination of Quality investing in the US to the Australian market. Specifically, a Quality score is computed as the aggregate of eight fundamental accounting metrics. An investment strategy investing in the highest (lowest) quality stock quintile, that is, Quintile 5 (1) generates an average annual Daniel, Grinblatt, Titman and Wermers (DGTW)-adjusted alpha of 6.37% (−7.98%), which is significant at the 5% level over April 2000–March 2010. A two-way segmentation based on size first, and quality second, reveals that the strong positive quality effect is primarily driven by small stocks, as the average DGTW-alpha for the top-quality tercile of small stocks is 14.02%, significant at the 5% level. Statistically significant positive DGTW-alphas are also determined for quality micro and large stocks. The quality analysis is also applied to a sample of Active Equity Mutual Funds' stock holdings. Weak evidence of the quality return premium is detected at the fund level.